HUBUNGAN ANTARA KADAR ADIPONEKTIN PLASMA DAN RESISTENSI INSULIN PADA PENDUDUK ASLI DESA TENGANAN PEGRINGSINGAN - KARANGASEM - Putrawan, Ida Bagus Putu; Suastika, Ketut (journal of internal medicine; Vol. 10, No. 3 September 2009, 2012)
The association between plasma adiponectin level and insulin resistance (IR), diabetes mellitus (DM)-2, hypertension, and cardiovascular disease have been reported previously. Adiponectin is expressed and produced by adipocyte cells, and plays critical role in the glucose metabolism. IR in the adipose cells increases lipolysis and release free fatty acid (FFA). Furthermore, inactivation of mitochondrial pyruvat dehydrogenase and Þ nally decreases glucose uptake through disturbance of insulin receptor signaling. To investigate the association between plasma adiponectin level and IR that was calculated by HOMA-IR, a cross sectional analytic study was conducted in Tenganan region, Bali from December 2007 to January 2008. As many as 80 participants whose age was 18 ! 65 years old were involved. The study involved 38 (47.5%) males and 42 (52.5%) females whose mean of waist circumference (WC) was 78.03 ± 10.88 cm, mean of plasma glucosa was 91.73 ± 8.84 mg/dl, median of insulin was 2.70 (2.00 ! 17.90)  IU/ml, median of HOMA-IR was 0.67 (0.38 ! 3.71), mean of HDL cholesterol was 58.93 ± 13.73 mg/dl, and mean of triglycerides was 145.64 ± 67.97 mg/dl, systolic blood pressure (SBP) was 70 ! 180 mmHg, and diastolic blood pressure (DBP) was 50 ! 100 mmHg. In this study, we found signiÞ cant correlation between plasma adiponectin level and IR (r = -0.370; p < 0.001). IR also signiÞ cantly correlation with central obesity (r = 0.361; p < 0.001), body mass index (BMI) (r = 0.381; p < 0.001), plasma HDL level (r = -0.327; p= 0.002), TG (r = 0.255; p = 0.011), and SBP (r = 0.198; p = 0.039). On multivariate analysis with multiple logistic regression, only central obesity has independent association with IR (B = 1.641; p = 0.023). Central obesity and sex were signiÞ cantly inß uential to the plasma adiponektin level (ß = -1.542; p = 0.035) dan (ß = 2.865; p < 0.001) respectively in which mean of the plasma adiponectin level in female (5.610 ± 2.815) was signiÞ cantly higher than that of male (3.365 ± 2.365; MD = -2.245; p < 0.001). Mean difference to plasma adiponectin level was signiÞ cantly inß uential of the plasma HDL level dan TG (MD = -10.500; p < 0.001) and (MD = 35.075; p = 0.020) respectively
Keywords: central obesity, plasma adiponectin level, insulin resistance